3D multiphysics simulation and analysis of a low temperature liquid metal magnetohydrodynamic power generator prototype. (October 2019) - Cosoroaba, Eva; Caicedo, Carlos; Maharjan, Lizon; Clark, Adam; Wu, Minxiang; Liang, Jingchen; Moallem, Mehdi; Fahimi, Babak
Abstract: Magnetohydrodynamic (MHD) power generation is an interdisciplinary process, which was studied heavily in the late 1960′s but interest soon subsided. However, the current socio-economic climate demands more diversity in renewable energy sources. MHD generators using liquid metal as the working fluid represent a viable option for this augmentation. Furthermore, the steady increase in accessible computational capabilities provides a powerful new tool for interdisciplinary modeling and multiphysics simulations. These factors suggest that this is an opportune time to reevaluate MHD power generation. This paper provides mathematical background as well as a detailed multiphysics model of a low temperature liquid metal MHD power generator built in COMSOL. Simulation details are provided in addition to a comparison to experimental results. The prototype studied in this paper is the first proof of concept of a permanent magnet excited liquid metal MHD generator using Gallium as its working fluid.